Komposisi, Keanekaragaman, dan Relung Ekologi Ikan di Plawangan Timur Segara Anakan, Jawa Tengah - Putri, Adinda Kurnia; Dewa, Andika; Listyani, Mei; Sahara, Laura Rose; Mahdiana, Arif; Kusuma, Rima Oktavia; Attaqi, Ahmad Naufal (Journal of Marine and Aquatic Sciences; Vol 9 No 2 (2023)DO - 10.24843/jmas.2023.v09.i02.p09, 2024)
Plawangan Timur Segara Anakan lagoon is known as the unique aquatic ecosystem that supports the life of aquatic organisms by providing nursery and feeding grounds. However, the Eastern Part of Segaran Anakan Lagoon is also utilized by many industrial and domestic activities that could degrade the quality and quantity of the aquatic ecosystem. This research aims to decribe the composition, diversity, and ecological niches of ichthyofauna from Eastern Segara Anakan Lagoon. Sampling was conducted on 29 June and 19 July 2023, using gillnets which have 1–2-inch mesh size. The diversity of ichthyofauna analyzed using the diversity indices while the distribution of the ichthyofauna were performed using Cannonical Correspondence Analysis (CCA). This study found 120 individuals of fish, that is comprised of 21 species, 19 families and 11 orders. The fish comprised of 18,34% adult and 81,66% juvenile. Most fishes were categorized as marine-freshwater-brackish resident and only I. japonica and S. commersoni species are true marine fishes. The diversity indices showed that Kali Panas station have the highest diversity indices and the lowest indices value were in Ujung Galang station. CCA showed that most fishes that are categorized as Marine, Marine-Reef-associated, and Marine, Brackish, Reef-Associated resident were found in high salinity waters.